Iarl and Iormun-; Arya- and Aryaman-: A Study in Indo-European Comparative Mythology - Bengtson, John D. (Comparative mythology, 2016)
In 1854 Martin Haug of Heidelberg suggested a root connection between the obscure German god Irmin and the minor Indic god Aryaman. Almost a century later (1952) Jan de Vries of Leiden agreed, with some reservations, and since then this theory has remained in dispute. In my study of this subject several arguments support the Haug - Vries hypothesis: Phonetic compatibility between OHG Irmin, ON Iǫrmun-, and Indic Aryaman (and between Nordic Iarl and Indic Arya). All are derivable from an IE root *H1er- ‘free man, clan member’. Phonetic and semantic parallels, such as between Old Swedish iarl and iarmun-, Old English eorl and eormen-; OIr aire and Airem; and OInd árya-, aryá-, ā́rya- and Aryamán-. Functional compatibility between German irmindiot ‘the collective human race’, Irminsūl ‘universalis columna’, OE eormen-wyrt ‘mallow’ (medicinal plant), etc., Indo- Iranian A(i)ryaman ‘god of marriage, hospitality, healing’, and the Irish hero Airem, all associated with Dumézil’s "first function." Patterning of personal names like OHG Irman-frīt, Irman-drūt, etc., like other IE names compounded from names of deities, e.g. ON Ás-ráðr (áss ‘god’ + ráðr ‘help[ed]’ = OHG Ans-rat). OI Aryama-rādha- ‘favored by Aryaman’ has a precise parallel in OHG Irmin-rat ‘helped by Irmin’. Cosmology: An old German name for the Great Bear constellation was Irmines- wagen ‘Irmin’s wagon’, and, according to Grimm, the Milky Way galaxy was *Irmin(es)-strasse ‘Irmin’s street’; cf. OI Aryamṇáḥ pánthāḥ ‘path of Aryaman’ = Milky Way. The argument that Irmin simply means ‘great, immense, elevated’ and is the sole remnant of the Indo-European middle participle in Germanic is implausible; the form Irmines- is clearly the genitive form of a name. The oldest sources and comparative mythology point to Irmin / Iǫrmun as some kind of divine or heroic entity closely connected with sovereignty, ancestry, and the collective life of the people (irmin-diot). In the post-Christian literary traditions of the Germanic and Celtic peoples the original patterns were transformed and distorted.